Selecting models with judgment - Simone Manganelli (European Central Bank (ECB), 2018)
A statistical decision rule incorporating judgment does not perform worse than a judgmental decision with a given probability. Under model misspecification, this probability is unknown. The best model is the least misspecified, as it is the one whose probability of underperforming the judgmental decision is closest to the chosen probability. It is identified by the statistical decision rule incorporating judgment with lowest in sample loss. Averaging decision rules according to their asymptotic performance results in decisions which are weakly better than the best decision rule. The model selection criterion is applied to a vector autoregression model for euro area inflation.
Keywords: C1; C11; C12; C13; 330; Statistical Decision Theory; Model Selection Criteria; Inflation Forecasting